Pharmacokinetics of omega-3 fatty acids in patients with severe sepsis compared with healthy volunteers: A prospective cohort study. Issue 3 (March 2020) - Parikh, Radhika; Bates, Jason H.T.; Poynter, Matthew E.; Suratt, Benjamin T.; Parsons, Polly E.; Kien, C. Lawrence; Heyland, Daren K.; Crain, Karen I.; Martin, Julie; Garudathri, Jayanthi; Stapleton, Renee D.
Summary: Background: Pharmacokinetics (PK) of pharmaceuticals and pharmaconutrients are poorly understood in critically ill patients, and dosing is often based on healthy subject data. This might be particularly problematic with enteral medications due to metabolic abnormalities and impaired gastrointestinal tract absorption common in critically ill patients. Utilizing enteral fish oil, this study was undertaken to better understand and define PK of enteral omega-3 fatty acids (eicospentaenoic acid [EPA] and docosahexaenoic acid [DHA]) in critically ill patients with severe sepsis. Materials and methods: Healthy volunteers (n = 15) and mechanically ventilated (MV) adults with severe sepsis (n = 10) were recruited and received 9.75 g EPA and 6.75 g DHA daily in two divided enteral doses of fish oil for 7 days. Volunteers continued their normal diet without other sources of fish oil, and sepsis patients received standard enteral feeding. Blood was collected at frequent intervals during the 14-day study period. Peripheral blood mononuclear cells (PMBCs) and neutrophils were isolated and analyzed for membrane fatty acid (FA) content. Mixed linear models and t-tests were used to analyze changes in FA levels over time and FA levels at individual time points, respectively. PK parameters were obtained based on single compartment models of EPA and DHA kinetics. Results: Healthy volunteers were 41.1 ± 10.3 years; 67% were women. In patients with severe sepsis (55.6 ± 13.4 years, 50% women), acute physiologic and chronic health evaluation (APACHE) II score was 27.2 ± 8.8 at ICU admission and median MV duration was 10.5 days. Serum EPA and DHA were significantly lower in sepsis vs. healthy subjects over time. PBMC EPA concentrations were generally not different between groups over time, while PBMC DHA was higher in sepsis patients. Neutrophil EPA and DHA concentrations were similar between groups. The half-life of EPA in serum and neutrophils was significantly shorter in sepsis patients, whereas other half-life parameters did not vary significantly between healthy volunteers and sepsis patients. Conclusions: While incorporation of n-3 FAs into PBMC and neutrophil membranes was relatively similar between healthy volunteers and sepsis patients receiving identical high doses of fish oil for one week, serum EPA and DHA were significantly lower in sepsis patients. These findings imply that serum concentrations and EPA and DHA may not be the dominant driver of leukocyte membrane incorporation of EPA and DHA. Furthermore, lower serum EPA and DHA concentrations suggest that either these n-3 FAs were being metabolized rapidly in sepsis patients or that absorption of enteral medications and pharmaconutrients, including fish oil, may be impaired in sepsis patients. If enteral absorption is impaired, doses of enteral medications administered to critically ill patients may be suboptimal.